Age-differentiated QALI Losses - Bernard M.S. van Praag; Ada Ferrer-i-Carbonell (Tinbergen Institute, 2002)
In this paper we evaluate the QALY loss, which may be assigned to the prevalence of specific chronic illnesses and physical handicaps. The analysis is based on an individual self-rating health satisfaction question asked in the British Household Panel Survey data set. This question provides a natural cardinalization of health utility .Our method is a refinement of the method introduced by Cutler and Richardson (1997). We extend their approach in two directions. First, the health utility loss caused by a specific illness is allowed to have a different impact on individuals depending on their age. The empirical analysis shows that there are indeed significant age effects. The second extension deals with the cardinalization procedure chosen by Cutler and Richardson. They implicitly assume a linear effect of underlying explanatory variables on the evaluation of health. Instead, we suggest a more natural cardinalization, which does not exclude non-linearities.
Keywords: I10; I12; 330; Chronic Illnesses; Health Satisfaction; QALY loss; Subjective Health; Gesundheitsökonomik; Index; Lebensqualität; Altersgruppe; Krankheit; Kosten-Nutzen-Analyse; Theorie; Großbritannien